The journey of the monument archives to the user friendly archives - Orosová, Martina (Moderna arhivistika, 2022)
In the article, the author presents one of the Slovak specialized public archives - the Monument Archives or the Archives of the Monuments Board of the Slovak Republic. Fonds and collections of the archives began to be created in 1919 in the Documentation Department, which in 1992 received the status of a specialized archives. At the end of the 1970s, the automation of document descriptions began. The first databases of archival collections were created. It was possible to migrate the structured data into a new archival information system that corresponds to international archival standards. The system is currently being modernized as part of the PAMIS project. The Monument Archives is the best archives in Slovakia, especially in providing services to the public and digitizing archival documents.
Keywords: archival information system; arhivski informacijski sistem; hramba spomenikov; monuments preservation; Slovakia; Slovaška; specialized archives; specializirani arhiv